Qualitative research on maternal care access among Arabic-speaking refugee women in the USA: study protocol - Sarah Yeo; Priscilla Magrath; Halimatou Alaofè; Abidemi Okechukwu (BMJ Open)
Background Refugees tend to have greater health needs and pre-existing medical conditions due to poor living conditions, lack of health services, exposure to a variety of risk factors, and a high level of stress and trauma prior to entry to a host country. Notwithstanding distinctive needs and inherent conditions, there is a paucity of literature on refugee maternal health, especially for Arabic-speaking refugee women resettled in the USA.Methods and analysis The paper delineates a qualitative study protocol to explore the experiences of Arabic-speaking refugee women in the USA when accessing maternal care. Informed by social cognitive theory, the study will employ two qualitative research methods; in-depth interviews and ‘go-along’ interviews with Arabic-speaking refugee women. Go-along interview will be used to elicit spatial experiences in situ to explore perceptions of environments among study participants and environmental and structural barriers. 20 refugee women who meet the inclusion criteria will be recruited through snowball sampling with support from community partners. Two researchers will code the transcription and fieldnotes using MAXQDA 2020 (VERBI Software, 2019). The analysis will involve deductive content analysis using a structured categorisation matrix based on the theory while also incorporating inductive codes that may emerge through the process.Ethics and dissemination The study has been reviewed and approved by the Human Subjects Protection Programme at the University of Arizona (IRB 2104716241). The study results will be condensed in a summary report, which will be shared with community partners, including refugee resettlement agencies and relevant staff at the state department. Also, community feedback will be garnered from the dissemination workshops to inform community discussions for actions and an intervention to address the identified needs.